Impacts of groundwater extraction on calcareous fen floristic quality. Issue 3 (27th April 2020) - Bart, David; Booth, Eric; Loheide, Steven P.; Bernthal, Thomas
Abstract: Groundwater withdrawal has increased over the past several decades throughout the U.S. Upper Midwest, yet impacts of pumping on groundwater‐dependent wetlands remain understudied. Here, we compared measures of floristic quality, hydrologic conditions, and nutrient availability in pairs of more‐impacted fens and less‐impacted fens throughout Wisconsin. Floristic quality was significantly lower in more‐impacted fens than in less‐impacted fens, the result of the disappearance of rare and specialist species and the increase in richness and cover of non‐native and weedy species. Plots within more‐impacted fens generally had lower root‐zone volumetric water content, greater depth to water table, and higher available nitrogen and phosphorus than within less‐impacted fens, although nonuniformly among or within sites. Lower volumetric water content predicted plot‐level declines in floristic quality, richness of rare or specialist species, an increase in the number of non‐native or problematic species, and an increase in cover of non‐native and problematic species. Our results strongly suggest that groundwater withdrawals have substantial negative impacts on nearby fen quality and furthering imperilment of several species they contain.